ACROMEGALY: A CONTEMPORARY REVIEW OF PATHOPHYSIOLOGY, DIAGNOSIS, AND TREATMENT APPROACHES (International journal of medical sciences, 2025)
Acromegaly is a chronic neuroendocrine disorder caused by excessive secretion of growth hormone (GH) and elevated insulin-like growth factor-1 (IGF-1), typically resulting from a GH-producing pituitary adenoma. The disease develops insidiously and is often diagnosed late, after irreversible systemic complications have developed. This article provides an expanded, evidence-based overview of the etiology, pathogenesis, epidemiology, clinical manifestations, diagnostic algorithms, and modern management strategies for acromegaly. Acromegaly is a rare disease, caused largely by a growth hormone (GH) pituitary adenoma. Incidence is higher than previously thought. Due to increased morbidity and mortality, if not appropriately treated, early diagnosis efforts are essential. Screening is recommended for all patients with clinical features of GH excess. There is increased knowledge that classical diagnostic criteria no longer apply to all, and some patients can have GH excess with normal GH response to glucose. Treatment is multifactorial and personalised therapy is advised.